Pandemic of COVID-19 and It’s Impacts - Sunder Singh; Rakesh Dhankhar; Vivek Kaushal; Ashok Chauhan; Rajeev Atri (Emerging Trends in Disease and Health Research Vol. 9, 2022)
COVID-19 pandemic, caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) was announced, and we had an unpredictable change in the way we were living socially and in our daily routine. The first victim affected by this virus was identified in Wuhan a city in China and Kerala in India. Children and adolescents were also greatly affected by the abrupt withdrawal from school, social life, and outdoor activities. Many of the population faced unexpected variations in their life. The stress they are subjected to directly affected their overall routine life. After the Covid-19 pandemic situation occurred every person in the world should be resolved timely by the government agencies at the Local, National, and International levels. But some dangerous effects are faced by every person in the world which are unforgettable for the entire life. These may be social, psychological, financial, human behavioral, environmental, and health effects. The basic objective of this research article is to critically analyse the impacts of COVID19 on kids, education, medical system and above all psychology of individuals and society as a whole. We pray to the Almighty that these types of pandemics should never be faced by people in the future.